Marmota (Marmota) camtschatica Pallas 1811 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Marmota (Marmota) camtschatica Pallas 1811 Marmota (Marmota) camtschatica Pallas 1811, Zoographia Rosso-Asiatica: 156. Type Locality: " Kamchatka " [Kamchatsk. Obl., Russia]. Vernacular Names: Black-capped Marmot. Subspecies:: Subspecies Marmota (Marmota) camtschatica subsp. camtschatica Pallas 1811 Subspecies Marmota (Marmota) camtschatica subsp. bungei Kastschenko 1901 Subspecies Marmota (Marmota) camtschatica subsp. doppelmayri Birula 1922 Distribution: E Siberia from Transbaikalia to Chukotka and Kamchatka (Russia), in several geographically isolated populations (Nikol'skii et al., 1991). Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Marmota (Steppan et al., 1999). Regarded as a synonym of marmota (Ellerman and Morrison-Scott, 1951; Rausch, 1953). Hoffmann et al. (1979) reviewed this and related species, and affirmed its specific status. Kapitonov (1978) concluded that morphological differences justified independent specific status for doppelmayeri , but Nikol'skii et al. (1991) showed similarity of vocalization between it and bungei , while the nominate form differed, and recommended that doppelmayeri be retained provisionally in this species. Boyeskorov et al. (1999) then showed that camtschatica and doppelmayeri were most divergent morphologically and immunologically, but the geographically intermediate Yakutian subspecies was also intermediate in these characters, and referred to the group as a whole as a superspecies. Steppan et al. (1999) found himalayana and sibirica to be sister species, and in the same clade as camtschatica . Lyapunova et al. (1992) regarded camtschatica as closely related to Nearctic marmots based on pattern of chromosome evolution, as had Hoffmann et al. (1979) based on morphology, but molecular data do not support this interpretation. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Sciuridae, pp. 754-818 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins ...